Obtaining bacterial cellulose from kombucha by replacing black tea with coffee husk tea - Jiménez Sánchez, Dolores Augusta; Merchán Sornoza, Jonathan Stalin; Tigre Chango, Jean Carlos (Ingeniería Química y Desarrollo, 2024)
The present investigation sought to obtain bacterial cellulose by inoculation of the Gluconacetobacter xylinus fungus present in the Kombucha drink by means of a static culture and with the replacement of black tea with an infusion of coffee husk. Two concentrations of 20 and 10 % sugar and 5 treatments of 0, 25, 50, 75 and 100 % substitution of coffee husk tea were evaluated. The rectangular reactors used were 1.5 L capacity. These were kept at room temperature for 15 days until the cellulose harvest. Both the fermented liquid and the membrane were evaluated for physical, chemical, mechanical and functional properties. The analysis of variance was carried out and the results indicate that the highest production of cellulose was with 10 % sugar and with a 75 % replacement of the coffee husk infusion. This treatment showed a biweekly yield of 25 % cellulose production, with better hardness properties and firm structure compared to the other treatments.
Keywords: Kombucha; bacterial cellulose; culture media; black tea; coffee husk